2020
DOI: 10.3389/fpls.2020.583590
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Chlorophyll a Fluorescence in Natural Compound-Induced Stress Detection

Abstract: Imaging of chlorophyll a fluorescence (CFI) represents an easy, precise, fast and non-invasive technique that can be successfully used for discriminating plant response to phytotoxic stress with reproducible results and without damaging the plants. The spatio-temporal analyses of the fluorescence images can give information about damage evolution, secondary effects and plant defense response. In the last years, some studies about plant natural compounds-induced phytotoxicity have introduced imaging techniques … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 135 publications
1
22
0
2
Order By: Relevance
“…When stress exceeded capacity, permanent photoinhibition occurred, which was detected by a decrease in the F v /F m value [46]. When the stress was strong enough, the PSII Φ PSII and the qP decreased, indicating that the ETR was inhibited [47]. In the present experiment, no significant changes in Φ PSII , ETR, or qP (except T337 in replanted soil in June and July) of T337, M26, or 12-2 after ARD were detected.…”
Section: Effect Of Ard On Fluorescence Parameters and Fluorescence Imaging Of Plant Leavesmentioning
confidence: 99%
“…When stress exceeded capacity, permanent photoinhibition occurred, which was detected by a decrease in the F v /F m value [46]. When the stress was strong enough, the PSII Φ PSII and the qP decreased, indicating that the ETR was inhibited [47]. In the present experiment, no significant changes in Φ PSII , ETR, or qP (except T337 in replanted soil in June and July) of T337, M26, or 12-2 after ARD were detected.…”
Section: Effect Of Ard On Fluorescence Parameters and Fluorescence Imaging Of Plant Leavesmentioning
confidence: 99%
“…The use of CFI allows the study of spatial and temporal heterogeneities in fluorescence emission patterns at the level of cells, leaves, plants, or a whole field, and has potential use to identify stress tolerance and for genotype screening in breeding programs ( Gorbe and Calatayud, 2012 ; Osório et al, 2014 ; Cen et al, 2017 ; McAusland et al, 2019 ; Sánchez-Moreiras et al, 2020 ). CFI is useful to asses stomatal patchiness and heterogeneity of photosynthetic activity ( Omasa and Takayama, 2003 ), overcoming the problems of point measurements due to the high variability at leaf level ( Ehlert and Hincha, 2008 ).…”
Section: Current Technologies and Strategies To Screen Grapevine Germplasmmentioning
confidence: 99%
“…It has been found that the best way to quantify water stress in plants is by measuring the reemittance of light from the plant surface. Empirical observations show that when the plant changes its photochemistry, it emits a chlorophyll fluorescence signal which falls under the range of 680 nm to 800 nm as a by-product of photosynthesis [ 8 ]. These fluorescence wave signals are recorded with the help of imaging devices, where reemitted light can be realised as a digital image, and mathematical analysis 4can be done for quantification of photosynthetic activity and water stress in a nondestructive manner [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%